ChemInform Abstract: A Highly Efficient Access to Enantiopure Tetrahydropyridines: Dual‐Organocatalyst‐Promoted Asymmetric Cascade Reaction. Issue 34 (1st August 2013) - Lin, Hua; Tan, Yu; Liu, Wen‐Jie; Zhang, Zhi‐Cheng; Sun, Xing‐Wen; Lin, Guo‐Qiang
Abstract A novel, highly efficient cascade process of Michael—aza—Henry—hemiaminalization—dehydration for the construction of enantiopure tetrahydropyridine derivatives is developed using a combination of proline silyl ether and cinchona alkaloid catalysts.